2023
DOI: 10.3390/v15061397
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Human Enterovirus Co-Circulations in Five Kindergartens in Bangkok between July 2019 and January 2020

Abstract: Human enterovirus causes various clinical manifestations in the form of rashes, febrile illness, flu-like illness, uveitis, hand–foot–mouth disease (HFMD), herpangina, meningitis, and encephalitis. Enterovirus A71 and coxsackievirus are significant causes of epidemic HFMD worldwide, especially in children aged from birth to five years old. The enterovirus genotype variants causing HFMD epidemics have been reported increasingly worldwide in the last decade. We aim to use simple and robust molecular tools to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Notably, the amplification primer used in Protocol 3 was a random primer, which might have been responsible for the increase in uncharacterized viruses found using this protocol. Despite the relatively wide use of SISPA-based methods for the characterization of the human virome [ 40 , 41 , 42 ] to address limitations inherent to virome determination, such as the lack of universal genes equivalent to the prokaryotic 16S rRNA gene, our results on the low replicability of the methodology based on this protocol urge us to be cautious regarding the reliability of this methodology. Theoretically, SISPA-based protocols, such as Protocol 3 in our study, because of their inconsistent reproducibility, require several replicates to be carried out in parallel and pooled.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the amplification primer used in Protocol 3 was a random primer, which might have been responsible for the increase in uncharacterized viruses found using this protocol. Despite the relatively wide use of SISPA-based methods for the characterization of the human virome [ 40 , 41 , 42 ] to address limitations inherent to virome determination, such as the lack of universal genes equivalent to the prokaryotic 16S rRNA gene, our results on the low replicability of the methodology based on this protocol urge us to be cautious regarding the reliability of this methodology. Theoretically, SISPA-based protocols, such as Protocol 3 in our study, because of their inconsistent reproducibility, require several replicates to be carried out in parallel and pooled.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the dynamics of genotype/subgenotype replacements have been documented in detail in several countries, e.g., China, Singapore, Malaysia, Taiwan, Vietnam, and Japan, during the past two decades 2 , 4 , 35 , 36 . Currently, the most common subgenotypes circulated in Thailand are B5, C1, and C4 in EV-A71 15 , 18 , 37 , 38 , while C4 is the most common in China and Vietnam 39 , 40 . The EV-A71 vaccines produced in China are prepared from the C4 subgenotype 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the emergence of the EV-A71 B5 virus was first recognized in 2006 and has been co-circulated with C4a in HFMD patients since 2008 until the present 15 . The current HFMD-associated-EV-A71 subgenotypes in Thailand comprised the subgenotypes C1, B5, and C4a 18 , 37 , 38 . The analysis of genetic evolution and epidemiological population dynamics demonstrated that the cyclical pattern of EV-A71 epidemics in Thailand was about 2–3 years, which was in line with those observed in several countries in the Asia–Pacific region 3 , 4 , 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can also be spread through respiratory secretions when infected individuals cough or sneeze. This dual transmission mechanism broadens the range of opportunities for the virus to infect new hosts [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%